Taxation and Development : Again - Keen, Michael (IMF Working Papers; Working Paper ;, 2012)
Issues of taxation and development, which have long been a central concern of the IMF, have attracted wider and renewed interest in the last few years. This paper reflects on three broad lessons of experience: that developing countries differ vastly in tax matters, and in ways that are less than fully understood; that the history of 'big ideas' in guiding tax reform for developing countries is decidedly mixed; and that the value of the emphasis often placed in this context on 'informality' is decidedly limited. It also asks whether ideas of 'state building' emphasized in some of the recent literature are likely to lead to practical advice much different from that commonly offered now.